(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2021)
The civil wars of the years 68‐69 represented a watershed in the history of the Roman empire. Even though they originated in some key provinces, they knew their final stage in Northern Italy, and especially near the site of Bedriacum, where the two most important battles of the war were fought. This study aims to analyse the impact of these conflicts on the local communities of Northern Italy, and the latter’s participation in the most crucial phases of the fights. Particularly, it follows the actions of L. Verginius Rufus, a man of consular rank who came from Milan and that twice refused an imperial acclamation, of the soldiers of North‐ Italian origins that fought in this area, and of Cremona, a town that due to its disputed loyalty was destroyed at the very end of the war